Desenvolvimento de metodologia segura para Pd0--carbonilação e síntese de novos compostos bis-1,2,3-triazólicos com atividade antitumoral - Wallace Júnio Reis (2020)
This work is composed by two different chapters. In the first chapter, a new methodology for carbonylation was developed, using bench-stable tablets (COtabs) to generate carbon monoxide in situ, without the use of glovebox apparatus. The carbonylation reactions were carried inside and outside of glovebox, and the results were compared, proving the applicability of the methodology. Twelve compounds were synthesized using the tablets and a two-chamber system known as COware. The compounds were obtained using carbonylative methods as Suzuki-Miyaura, Sonogashira, Heck-Mizoroki and aminocarbonylation, with aryl or heteroaryl halogenated substrates. Among compounds obtained, a 5-iodo-1,2,3-triazole derivative represents an important intermediate to the synthesis of carbonylated compounds obtained via click chemistry. In the second one, a serie of nineteen novel bis-1,2,3-triazole-1,4-disubstituted compounds containing aliphatic and oxygenated linkers, with several substituents on the 1,2,3-triazole ring, were synthesized. All the compounds were obtained by 1,3-dipolar reaction between an azide (aliphatic or oxygenated) and a terminal alkyne (with several substituents) catalyzed by Cu(I), using click chemistry methodology. The compounds were evaluated in antitumor assays against human tumor cell lines (ATCC HTB-26 breast adenocarcinoma and TOV-21g ATCC ovary adenocarcinoma CRL-11730) and normal cells WI-26VA4 (pulmonary fibroblast ATCC CCL -75). The better MIC and IS results were obtained in vitro assay for the compounds 114j and 114q, which are promising antitumor agent candidates that are in the study phase of their mechanism of action. The characterization of all the compounds was also done by melting point, IR region spectroscopy and 1H NMR, 13C and DEPT-135 and high resolution mass spectrometry.